The Filippi's Glands of Giant Silk Moths: To Be or Not to Be? - Sehadova, Hana; Zavodska, Radka; Zurovec, Michal; Sauman, Ivo (Insects, 2021)
The Filippi's glands (FGs), formerly "Lyonet's glands", are paired accessory organs associated with the silk glands. They are unique to Lepidoptera caterpillars and their exact role is not clear. The FGs are thought to be involved in the construction of a silk cocoon in bombycoid moths. FGs can differ in size and shape, therefore, in this study we attempt to find a correlation between FG morphology and phylogenetic position within the Bombycoidea. We use light and electron microscopy to examine the presence and morphology of FGs in a range of wild (giant) silk moths and several related species. Our results confirm that the majority of studied silk moth species have complex type of FGs that continuously increase in size during larval development. We identified several species of giant silk moths and two hawk moth species that completely lack FGs throughout their larval development. Finally, in several hawk moth species in which FGs are well developed during the first larval stage, these glands do not grow and remain small during later larval growth. Our results suggest that FGs are not critical for spinning and that loss of FGs occurred several times during the evolution of saturniids and sphingids. Comparison of FGs in different moths is an important first step in the elucidation of their physiological significance.
Keywords: silk; Saturniidae; Pyralidae; Sphingidae; Filippi’s glands; Bombyx mori